Two in a bed : the social system of couple bed sharing - Rosenblatt, Paul C. (State University of New York Press, 2006)
"Two in a Bed includes interviews with more than forty bed-sharing couples as they candidly discuss winding down and waking up, cold feet and tucked sheets, who sleeps near the door and who gets pushed to the edge, snoring, spooning, sleep talking, sleep walking, and the myriad other behaviors we negotiate in falling asleep, staying asleep, and waking up each morning beside a partner. In addition to exploring the routines and realities of sharing a bed with another person, these interviews reveal important information about sleep, relationships, and American society. Stressing the intricacy and importance of a previously unremarked activity, Rosenblatt's Two in a Bed shows that sleep should no longer be viewed solely as an individual phenomenon."--Jacket.